An environmental management experience to control wildfires in the mid-mountain mediterranean area: Shrub clearing to generate mosaic landscapes. (July 2022) - Lasanta, Teodoro; Cortijos-López, Melani; Errea, M. Paz; Khorchani, Makki; Nadal-Romero, Estela
Abstract: The Mediterranean mountains have undergone an intense process of land abandonment since the mid-20th century, with far-reaching changes to the landscape (homogeneity and an increase in combustible material), which, combined with the rise in temperatures, increases the size and frequency of wildfires. This increase has taken place despite technical advances in detecting and fighting fires, which suggests that prevention measures should be improved. Shrub clearing is a practice used in some areas of the Mediterranean mountains to prevent wildfires. This paper presents the results from a study carried out in the Iberian mountain range in La Rioja (Spain), which is representative of mid-Mediterranean mountain landscape due to the wide areas of abandoned land and the highly homogeneous environment dominated by shrubs. From 1986, the Regional Government of La Rioja launched the Plan for Shrub Clearing (PSC) to control fires and promote extensive livestock farming. Between 1986 and 2020, 28.4% of the shrub surface in the study area was cleared, which helped to create a more fragmented and diverse landscape, and drastically reduced the total burned area (average of 1060 ha/year between 1968 and 1986, against 221.7 ha/year between 1987 and 2020). The results obtained in this article show that the PSC, together with extensive livestock farming, is a useful practice in managing homogeneous landscapes. The PSC creates a mosaic landscape, reduces the fuel load, helps to fight fires and contributes to the provision of ecosystem services. The results can help land managers to implement public policies aimed to reduce environmental hazards, such as wildfires and, thus, ensure that natural resources providing assets and services to the public are maintained. Highlights: Combining shrub clearing and extensive livestock is a preventive measure against wildfires. Shrub clearing creates a mosaic landscape, with less combustible and facilitates fire suppression. Eliminate shrubland decreases the traditional farmer fires. The mean burned area decreases about 73.1%/year due to shrub clearing and livestock. Public policies to support extensive livestock enhance ecosystem services.